Archaeological Wood from Medieval Monuments of Primorye in the Russian Far East - Nina V. Leshchenko (Археология евразийских степей, 2023)
The article considers the archaeological wood from Primorye medieval sites of the time of Bohai state (698–926) and post-Bohai period. Materials from collections of open complexes are used: Nikolayevka-II, Kraskino settlements, Konstantinovka-I unfortified settlement, as well as the closed – Kraskino burial ground. The wood was extracted both from archaeological objects, structures (well shafts, fences, details of a platform in a tiled chamber, boarding the walls of granaries, wooden columns, structural elements of burials), and objects made of wood (knife handles, tools, combs, dishes, horse trapping parts) were studied. The methods and techniques of surface treatment, as well as the tools used, are considered. Definitions of wood species have been made. Paleoxylotonic analysis of wood remains from the barrow No. 1 of the Kraskino burial ground was conducted. A spore-pollen analysis of samples from sections of this object was made. The results of analyses of samples, produced during microscopic section of wood are given. For the first time sources on the problem of interest have been collected together. Photoanalytical and trace evidence methods were applied in treatment of materials. Andonstar A1 long-focus digital USB microscope with 500x magnification and 2 MP sensor was used in the work.